Board Characteristics and Sustainability Performance: Evidence from Indonesia’s Energy Sector (E-Jurnal Akuntansi, 2025)
This study provides empirical evidence on the effect of board characteristics—specifically board size, board gender diversity, board educational background, and board meeting frequency—on the sustainability performance of energy sector companies listed on the Indonesia Stock Exchange over the 2021–2023 period. Multiple linear regression analysis was employed, using a sample of 26 energy firms (78 firm-year observations) selected through purposive sampling. The findings indicate that board educational background and board meetings have a positive and significant effect on sustainability performance, while the other board attributes show no such effect. These results are consistent with stakeholder theory, which underpins the link between board characteristics and sustainability performance by suggesting that more competent and actively engaged boards are better able to respond to stakeholder expectations regarding sustainability.